Bunuh Diri pada Remaja: Faktor Risiko dan Pencegahan - Pusporani, Mina; Nuryanti, Lusi; Safitri, Dhea Azra (Prosiding University Research Colloquium, 2023)
enters for Disease Control and Prevention (CDC) study shows that suicide is the second-leading cause of death among children and adolescents aged 10 to 17 years. Ten years ago, suicide was the fourth-leading cause of death in children aged 10 to 17 years. The increasing incidence of suicide attempts and suicide deaths, especially among adolescents, points to an urgent need to gain a better understanding of the risk factors leading to increased suicide risk and to design innovative interventions for suicide in children and adolescents. To obtain a complete picture of the risk factors for suicide in adolescents and recent interventions, we reviewed the literature in the form of journals in the last five years. We included 31 journal articles on youth suicide that were collected through Publish or Perish software and the ProQuest database. Risk factors for suicide in adolescents can be classified, among others, as mental illness, psychosocial factors, sociodemographic factors, biological factors, and other risk factors. To prevent suicide attempts and suicides, various preventive measures can be taken and need collaboration at the community, subpopulation, and individual levels.